2019
DOI: 10.1111/jog.14090
|View full text |Cite
|
Sign up to set email alerts
|

BRCA mutation frequency and clinical features of ovarian cancer patients: A report from a Chinese study group

Abstract: Aim: Subjects with germline BRCA1/2 mutations ( gBRCAm) have an increased risk of developing breast cancer and ovarian cancer. At present, knowledge of BRCA1/2 mutation frequency in Chinese patients with ovarian cancer is still insufficient, and the detailed clinical information of these patients is poorly understood. Methods: A total of 547 unselected ovarian cancer patients were enrolled, and their gBRCAm status was detected. Clinical characteristics including age, personal and family history, histopathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 38 publications
1
15
2
Order By: Relevance
“…In previous literature reports, the mutation rate of BRCA1/2 in Chinese ovarian cancer patients was between 16.7-28.5% (11,22,23), while in our study, the proportion of patients with BRCA1/2 mutation was as high as 42.0%. In addition, BRCAmut patients have a lower age of onset and a higher proportion of fully sensitive patients (PFI > 12 months).…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…In previous literature reports, the mutation rate of BRCA1/2 in Chinese ovarian cancer patients was between 16.7-28.5% (11,22,23), while in our study, the proportion of patients with BRCA1/2 mutation was as high as 42.0%. In addition, BRCAmut patients have a lower age of onset and a higher proportion of fully sensitive patients (PFI > 12 months).…”
Section: Discussioncontrasting
confidence: 64%
“…Patients with BRCA1/2 mutations usually have longer PFI, and platinum-based chemotherapy after relapse is more effective than patients without BRCA1/2 mutations (10,11). Whether BRCAmut patients will bene t from SCS is controversial.…”
Section: Introductionmentioning
confidence: 99%
“…DSBs can only be repaired through homologous recombination (HR) repair or non-homologous end joining (NHEJ). As previously discussed, HR is essential for the error-free repair of DSBs and requires functional BRCA1/2 proteins (Offit, 2006;Palomba et al, 2014;Vos et al, 2018;Bu et al, 2019). In HR deficient tumors, such as BRCA1/2 mutated tumors, the inhibition of PARP yields DSBs which can only be repaired through NHEJ.…”
Section: Replication Fork Stalling and Parp Trappingmentioning
confidence: 99%
“…Interestingly, the top recurrently detected mutations varies between different studies, including the BRCA1:c.1081del, c.964del, c.3770_3771del, c.2371_2372del and c.5470_5477del etc. (12,(19)(20)(21); this is probably caused by the different ethnic origins and geographic locations of the included patients. Several studies have reported the BRCA1:c.5470_5477del as the most frequently detected mutation in Chinese OC patients; of note, the patients enrolled in these studies were mainly from northern China (13,20,22), and studies on the southern Chinese revealed different top mutations (12,19,21).…”
Section: Discussionmentioning
confidence: 99%
“…( 12 , 19 21 ); this is probably caused by the different ethnic origins and geographic locations of the included patients. Several studies have reported the BRCA1 :c.5470_5477del as the most frequently detected mutation in Chinese OC patients; of note, the patients enrolled in these studies were mainly from northern China ( 13 , 20 , 22 ), and studies on the southern Chinese revealed different top mutations ( 12 , 19 , 21 ). In this study, almost all the patients are from Henan, the central region of China and the origin of Chinese civilization.…”
Section: Discussionmentioning
confidence: 99%